2015
DOI: 10.1002/job.2046
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new scale to measure subjective career success: A mixed-methods study

Abstract: Summary Career success is a main focus of career scholars as well as organizational stakeholders. Historically, career success has been conceptualized and measured in an objective manner, mainly as salary, rank, or number of promotions. However, the changing nature of work has also necessitated a change in the way many employees view success, adding a more subjective component. Although there has been theoretical discussion and calls to develop a comprehensive measure of subjective career success, no contempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
270
0
22

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(337 citation statements)
references
References 85 publications
5
270
0
22
Order By: Relevance
“…However, the moderate positive relationship between family orientation and career satisfaction is important from a work-home perspective on careers (Greenhaus & Kossek, 2014) because the result implies that employees who consider family issues when managing their career report higher career satisfaction. This finding is in line with the result from Shockley et al (2015) that having a satisfying personal life is a key dimension of subjective career success for many people. Moreover, other research suggests that subjective career success is higher for people who adopt a whole-life perspective on career development, possibly because they can better satisfy their various needs across life roles which leads to a more positive evaluation of their career (DiRenzo et al, 2015).…”
Section: Nwo As Predictors Of Career Successsupporting
confidence: 90%
See 2 more Smart Citations
“…However, the moderate positive relationship between family orientation and career satisfaction is important from a work-home perspective on careers (Greenhaus & Kossek, 2014) because the result implies that employees who consider family issues when managing their career report higher career satisfaction. This finding is in line with the result from Shockley et al (2015) that having a satisfying personal life is a key dimension of subjective career success for many people. Moreover, other research suggests that subjective career success is higher for people who adopt a whole-life perspective on career development, possibly because they can better satisfy their various needs across life roles which leads to a more positive evaluation of their career (DiRenzo et al, 2015).…”
Section: Nwo As Predictors Of Career Successsupporting
confidence: 90%
“…This view is supported by meta-analytic research that has shown that occupational commitment (Lee et al, 2000), job involvement (Brown, 1996), and organizational commitment (Meyer, Stanley, Herscovitch, & Topolnytsky, 2002) are all positively related to overall job satisfaction and to an aggregate of different indicators of subjective career success (Ng & Feldman, 2014b). This result may occur because stronger work commitment leads to more invested resources in the working role that, in turn, favors the attainment of subjectively valued career outcomes (e.g., recognition, challenging work, influence) (Shockley, Ureksoy, Rodopman, Poteat, & Dullaghan, 2015). Accordingly, to the extent that NWO leads to a depletion of resources that could alternatively be invested in the work role, NWOs might be negatively related to career satisfaction.…”
Section: Nwos and Career Successmentioning
confidence: 90%
See 1 more Smart Citation
“…In this case, meaningful work may relate directly to these outcomes but only as one of many factors in people’s lives that predict wellbeing, making relations between meaningful work and general wellbeing relatively smaller. This is consistent with meaningful work’s correlations to life satisfaction (0.33–0.49; Arnoux‐Nicolas et al, , Shockley et al, ), negative affect (−0.04 to −0.32; Allan et al, ; Steger et al, ), and general health (0.24–0.50; Arnold and Walsh, , Soane et al, ), which have been small to large in effect size.…”
Section: Introductionsupporting
confidence: 75%
“…Several authors consider success to be multidimensional (Hennequin, ; Shockley, Ureksoy, Rodopman, Poteat, & Dullaghan, ). Expectations are not uniform across employees in terms of their professional success (Hennequin, ).…”
Section: Objective and Subjective Career Successmentioning
confidence: 99%